Determinants of organizational practices and research culture for the enhancement of research performance in Malaysian universities - ASRIZAM ESAM; SUHAIMI AB RAHMAN; DAHLIA ZAWAWI; AWIS QURNI SAZILI; NIK ROSNIWATI ISMAILYUSNITA TUGIRAN; YUSHAIDA YUSOFNORLIYANA KAMARUDIN (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: Through a focus on Universiti Putra Malaysia, one of the best Research Universities in Malaysia, especially in agriculture fields, this study examines the similarities and differences of organisational practises and research culture among academic staff that influence the research performance in Malaysian public universities.Method: Forty professors and lecturers in science and technology, as well as the social sciences, arts, and humanities, participated in a qualitative focus group interview.Findings: Research performance factors must be determined after considering the researchers’ perspectives and experiences. This research reveals that the academic staff agree on the existence of 5 possible tangible and 8 intangible factors that contribute to research performance, with one intangible factor emerging as a novel factor that will affect research performance. These things can be used as a yardstick against which other things are measured.Implications/Novel Contribution: This research fills a gap in the existing literature by illuminating Malaysia’s public universities’ institutional norms and research ethos.